On the mechanics of intracranial aneurysms walls: numerical assessment of the inﬂuence of tissue hyperelastic laws and heterogeneity and the major role played by curvature on pathways to rupture - Oliveira, Iago Lessa (2022)
Intracranial aneurysms (IAs) are abnormalities formed in the cerebral arteries characterized by outpouching regions of their walls. The danger with these lesions occurs if they rupture, which causes intracranial hemorrhage and possibly leads to the death of the patient, presenting a mortality rate as high as 50 %. The rupture event is hard to predict, though, and, currently, surgical treatments also pose risks to the patient. Numerical simulations of the blood flow inside IAs have been extensively used to study them because of the well-known connections between hemodynamics and their inception, growth, and rupture. Physically, although it should be modeled as a Fluid-Solid Interaction (FSI) problem, the majority of those works have solely focused on the hemodynamics while either ignoring the wall tissue motion entirely, through rigid-wall modeling, or using limited assumptions for it. One possible explanation is the scarcity of measurements of their wall mechanical properties and also its thickness, which limits the use of better modeling options. Consequently, few works have investigated the impact of tissue modeling on their mechanical response, an important endeavor to try to predict the likelihood of rupture, because it is a wall-exclusive event that theoretically depends on the level of stress. In this context, this work investigated the influence of different hyperelastic laws and the material properties and thickness heterogeneity on the wall mechanics of IAs, given their rupture status. Pulsatile numerical simulations with patient-specific vascular geometries harboring IAs were carried out using the one-way fluid-solid interaction solution strategy implemented in solids4foam, an extension of OpenFOAM®, in which the blood flow is solved and applied as the driving force of the wall motion. First, it was found that different wall morphology models yielded smaller absolute differences in the mechanical response than different hyperelastic laws. Second, the stretch levels of IAs walls were more sensitive to the hyperelastic laws and material constants than the stress, especially for ruptured IAs, allowing the identification of these by the higher stretch levels instead of stress levels. Additionally, the morphology variable that best correlated with regions of high stress and stretch was the wall curvature. Finally, these findings could be used to guide modeling decisions on IA simulations and also suggest new metrics based on the wall curvature to predict the likelihood of rupture.